Analisis Berita Pertanian Koran Kampus IPB Dari Perspektif Agenda Setting Theory (Kasus Mahasiswa SKPM 2009 dan AGH 2008) - Agus Sandra; Amiruddin Saleh (Institut Pertanian Bogor, 2013)
Abstract Agenda setting indicate a relationship between the media and the public in terms of determining whether a message is important or not. But, there are not real if the media haven’t strong influences. Analysis of agricultural news in IPB Campus Newspapers prove that the media hasn’t influenced IPB students to pay attention about the agricultural issue. The results of this study found the media assess the agriculture news is not important. That caused by the quantity was low compared to the other news, although their was put the agricultural news on front pages. The survey showed that the agricultural information was reported by IPB Campus Newspapers causses important by the public. That was known by asking the public to assess the level of news interest, rate the agricultural news, and also choose the agricultural news than the other news. This studi also showed that there was’nt real differences of students from two disciplines in assessing the public agenda of agricultural news in Campus Newspapers IPB, which inferential statistical analysis showed the results of T2Hotelling of 1,0782 (p>0.05).Keywords: media agenda, public agenda, agenda setting